Teacher Performance As Assessed in Terms of Workload, Emotional Intelligence, Training and Use Of Technology - Fatma Luvy Purborini; Istiatin Istiatin; Kartika Hendra Titisari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine and analyze the influence of workload, emotional intelligence, training, and technology utilization on teacher performance at Ta'mirul Islam Elementary School and Ta'mirul Islam Inovatif Elementary School under the auspices of the Ta'mirul Masjid Tegalsari Surakarta Foundation. The research method used is quantitative with a survey approach to 87 respondents through an online questionnaire (Google Form). The data analysis technique uses multiple linear regression analysis to test the relationship and influence between variables. The results of the study indicate that workload, emotional intelligence, training, and technology utilization partially and simultaneously have a positive and significant effect on teacher performance. The conclusion of this study confirms that proportional workload management, increasing emotional intelligence, implementing continuous training, and optimizing technology utilization are key factors in improving teacher performance at the Ta'mirul Masjid Tegalsari Surakarta Foundation.